Real Options Approach to the Pre-Closing Process of a Merger and Acquisition: An Exploratory Study in the French Context - Flah, Ines Ben (Copernican Journal of Finance & Accounting, 2024)
The research objective of the article is to understand the real options’ generatingprocess during the various stages of the mergers and acquisitions (M&A) projects. In fact, the significant increase in the number of publications on M&A using thereal option method from the mid 1990’s to today contrasts with the low average rateof its utilization by managers. In Europe, only 6% of CFOs in large companies claim touse the real options method in their capital budgeting process (Horn, Kjærland, Molnár& Steen, 2015). This is due to a lack of familiarity with this method. On this basis,we will resume the main theoretical work concerning the optional approach in M&A. The applied research method aims to enrich and complete this literature by identifyingthe different types of real options related to M&A projects based on a qualitativeand exploratory research study and carried out with experts involved in the FrenchM&A market (investment bankers, merger and acquisition consultants, strategy advisor,financial transaction services manager and accounting experts). By analyzing thediscourse of these experts, the outcome of the research identifies real options in all thephases leading up to the closing of an M&A operation. The main conclusions of this research highlight the qualitative role of real options in managing the pre-closing processof a M&A by breaking down each stage of this process into a multitude of options.